Pengaruh Perceived Ease of Use, Perceived Usefulness, Attitude toward Using dan Sales Promotion terhadap Repurchase Intention Tiket Bioskop Pengguna Aplikasi TIX-ID - Haris Kristanto; Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2021)
The purpose of this study is to examine the influence of perceived ease of use, perception usefulness, attitude towards using, and sales promotion on repurchase intention Cinema 21 tickets through the TIX-ID application. This research is limited to consumers who have used the TIX-ID application to purchase cinema tickets. The sampling method used was non-probability sampling method with convenience sampling techniques, and with 103 respondents. The data was analysed by using PLS-SEM and estimated by using SmartPLS 3.2.9 as software. The results showed that perceived ease of use and perceived usefulness significantly affect attitude toward using. Sales promotion did not have any significant effect on repurchase intention, while attitude toward using significantly affected the repurchase intention of consumers towards Cinema 21 tickets through the TIX-ID application. Tujuan penelitian ini yaitu untuk menguji pengaruh dari perceived ease of use, perceived usefulness, attitude toward using, serta sales promotion terhadap repurchase intention tiket bioskop 21 melalui aplikasi TIX-ID. Penelitian ini dibatasi pada konsumen yang sudah pernah menggunakan aplikasi TIX-ID untuk melakukan pembelian tiket bioskop. Metode sampling yang digunakan adalah non-probability sampling dengan teknik convenience sampling, dan dengan 103 responden. Pengolahan data menggunakan PLS-SEM dan diestimasi menggunakan software SmartPLS 3.2.9. Hasil penelitian menunjukan bahwa perceived ease of use dan perceived usefulness berpengaruh signifikan terhadap attitude toward using. Sales promotion tidak memiliki pengaruh yang signifikan terhadap repurchase intention, sedangkan attitude toward using berpengaruh secara signifikan terhadap repurchase intention tiket bioskop oleh konsumen melalui aplikasi TIX-ID.